Experimental and Numerical Investigation of Temperature Development of Ohmic Heating Cured Nonmass Concrete under Subzero Temperature. (15th December 2021) - Qi, Beimeng; Zhou, Zheng; Tian, Weichen; Ouyang, Mingzhe; Wang, Xiaocheng; Shi, Qiang; Wang, Ye; Sun, Yang; Wang, Wei
Abstract : In this paper, carbon fiber/carbon nanofiber strengthening nonmass concrete slab was designed, and ohmic heating (OH) curing was used to promote the strength formation of the slab under −20°C. COMSOL multiphysical field coupling program has been used to simulate the heating process of nonmass concrete slabs under different conditions. COMSOL analysis results showed that the optimal loading power density of OH cured sample under −20°C was 1000 W/m 2 ∼1200 W/m 2 . Moreover, numerical analysis results were experimentally validated by the multipoint temperature measurement method. Furthermore, the mechanical properties showed that the compressive strength of the sample cured by 2 days OH curing at −20°C reached up to 48.2 MPa. SEM analysis exhibited that OH curing could improve the interfacial transition zone (ITZ) between the fiber and the matrix, leading to a denser microstructure. This study proved that COMSOL program could provide good theoretical guidance for OH cured nonmass cement concrete under subzero temperature. This work establishes an accurate guideline for electric power supplementation, laying a solid foundation of winter construction with high efficiency and low energy consumption.